New genetic variant in the SERPINC1 gene: hereditary Antithrombin deficiency case report, familial thrombosis and considerations on genetic counseling - Margarita E. Polyak; Elena V. Zaklyazminskaya (BMC, 2020)
Abstract Background Inherited deficiency of the antithrombin (hereditary antithrombin deficiency, AT deficiency, OMIM #613118) is a relatively rare (1:2000-3000) autosomal-dominant disorder with high risk of venous thromboembolism. Mutations in the serpin family C member 1 gene (SERPINC1) can lead to Quantitative (type I) and Qualitative (type II) types of antithrombin deficiency. We describe a new genetic variant in the SERPINC1 gene and our approach to variant interpretation. Case presentation We observed a 29 y.o. female proband with the episode of venous thrombosis at the age of 18 and family history of thrombosis. The antithrombin level in our patient was low, 44-48% (AT deficiency type I). A new genetic variant c.662G > C (p.W221S) in the SERPINC1 gene was detected in proband and affected father but was absent in healthy sister. We used in silico tools to evaluate the possible impact of p.W221S variant on protein structure and function. In mutated SERPINC1 protein a new N-linked glycosylation site is formed, however, it is unclear if the glycosylation at 219-221 site is possible. Conclusion The proband was provided with appropriate genetic counseling and referred to a hematologist. Based on all the evidence we classify the p.W221S variant as variant of unknown clinical significance. In this paper we discuss some aspects of genetic counseling, variant interpretation and thromboembolic prophilaxis.